The Impact of Digital Literacy And Islamic Financial Literacy on Paylater Usage Decision in Serang District: Trust in Financial Institutions As A Mediating Variable - Mukti, Titania -; Marlia, Sri -; Najib, Mohamad Ainun; Abduh, Muhammad - (FEB Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to examine the influence of digital literacy and Islamic financial literacy on the decision to use paylater, with trust in financial institutions as a mediating variable. The method used in this study is a quantitative approach with a survey involving 228 respondents selected by the purposive sampling method with certain criteria. Data analysis was carried out using Structural Equation Modelling (SEM) with SmartPLS software. The results of the study show that digital culture and trust in financial institutions have a significant effect on the decision to use paylater services partially with the probability value of each prob. 0.000 and prob. 0.046. Meanwhile, digital ethics and digital skills did not have a significant effect on the decision to use paylater (prob. > value 0.05). In addition, Islamic finance skills (prob. 0.000) and Islamic financial knowledge (prob. 0.000) affect trust in Islamic financial institutions. In terms of moderation effect, this study found that only Islamic finance skills moderated the influence of trust in Islamic financial institutions on paylater usage decisions (prob. 0.048), while digital safety and digital skills did not show a significant moderation effect